Principal’s Strategy in Improving the Quality of Teachers’ Teaching - Mardiana, Linda; Ahyani, Nur; Nazaruddin, Nazaruddin (Journal of Social Work and Science Education, 2023)
This study aims to determine the principal’s strategy for improving the quality of teacher teaching at SD Negeri 11 Indralaya. This research used the descriptive-qualitative method. Data collection was carried out using interview and observation techniques, including data analysis techniques. For data validity using the method of triangulation. Data samples in this study are principals, vice principals, and teachers. The results showed that (1) the principal’s strategy in improving the quality of teacher teaching carried out by the principal of SD Negeri 11 Indralaya (a) provided laptop facilities as learning media (b) provided opportunities for teachers to attend training seminars outside (c) provided internet facilities (d) following the rules; (2) the obstacles faced by the principal regarding the low level of teacher professionalism of the teacher himself; (3) the solution faced by the principal of SD Negeri 11 Indralaya in overcoming the obstacles to improving the quality of teacher teaching is to entrust full responsibility to several teachers who are less effective.